Pengaruh NPF, NOM dan FDR Terhadap Pembiayaan Murabahah dengan DPK Sebagai Variabel Moderating - Farianti, Rizki; Pramuka, Bambang Agus; Purwati, Atiek Sri (MALIA: Journal of Islamic Banking and Finance, 2019)
This study aims to determine the Non Performing Financing (NPF), NetOperating Margin (NOM) and Financing to Deposit Ratio (FDR) on MurabahahFinancing with Third Party Funds (TPF) as the Moderating Variable. Thepopulation in this study are Islamic Banks that publishes their financialstatements to Otoritas Jasa Keuangan (OJK) and each website of Islamic Banksfor the period 2013 to 2017, with a sampling technique that is purposivesampling, the samples taken were 8 Islamic Banks in Indonesia obtained wereanalyzed by moderating regression analysis technique. The results of this studyindicate that: (1) Non Performing Financing (NPF) does not negatively affectmurabahah financing at Islamic Banks; (2) Net Operating Margin (NOM) hasa positive effect on murabahah financing at Islamic Banks; (3) Financing toDeposit Ratio (FDR) has a positive effect on murabahah financing at IslamicBanks; (4) Third Party Funds (DPK) do not moderate the negative influence ofNPF on murabahah financing at Islamic Banks; (5) Third Party Funds (DPK)strengthen the positive influence of NOM on murabahah financing at IslamicBanks; (6) Third Party Funds (DPK) strengthen the positive influence of FDRon murabahah financing at Islamic Banks. The implication of this research isthe result of this study can be used as an effort to increase murabahahfinancing. To increase the amount of murabahah financing, managerial inIslamic Banks in Indonesia need to prioritize policies related to Net OperatingMargin (NOM), Financing to Deposit Ratio (FDR) and Third Party Funds(DPK).